SIMBOLISME HAJI ORANG BUGIS MENGUAK MAKNA IBADAH HAJI BAGI ORANG BUGIS DI BONE SULAWESI SELATAN - Subair Subair (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
Hajj experiences fluidity when interpreted by Bugis, which has implications for meaningful symbolic aspects, tends to be mystical and contemplative. For the Bugis, the pilgrimage is a symbol of the transformation of one's selfhood, where hajj means reaching the highest position that a person can attain. Using hajj attributes is a necessity. Attributes such as hajj clothing are highly valued because they have been blessed through the mappatoppo ritual. Aside from being a symbol of Hajj graduation, mappatoppo is also believed to be a condition of hajj perfection which is related to the ability to use the title of hajj and the appropriateness of wearing hajj clothing. The use of hajj clothing must be carried out at public events, if not, it is considered to be an insult to the status of the study. On the contrary, wearing hajj clothing by people who are not public pilgrimage is considered to be a person who has no shame (to de 'gaga siri'na), and undoubtedly will be sanctioned in the form of reproach and exclusion in social interaction.